The 25th Biennial International Congress on Thrombosis 2018
DOI: 10.3390/proceedings2090533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Plasmic Score for the Prediction of Adamts13 Activity in Patients with Thrombotic Microangiopathies

Abstract: Abstract:The PLASMIC score for the prediction of a likelihood of a severe ADAMTS13 deficiency represents a valid pre-test diagnostic tool to identify patients with thrombotic thrombocytopenic purpura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In the original study about the PLAMSIC score, the specificity in the internal validation cohort is 31%, 58.44% in the external validation cohort. The specificity is 55.68%, 51.78%, 60% and 25.6% in another four validation cohorts study (Table ) . These diversities between our and other validations may be caused by the low percentage of patients in low‐risk group (0‐4), 5.26%.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…In the original study about the PLAMSIC score, the specificity in the internal validation cohort is 31%, 58.44% in the external validation cohort. The specificity is 55.68%, 51.78%, 60% and 25.6% in another four validation cohorts study (Table ) . These diversities between our and other validations may be caused by the low percentage of patients in low‐risk group (0‐4), 5.26%.…”
Section: Discussionmentioning
confidence: 47%
“…In order to solve this difficulty, many doctors and scientists had tried to use available clinical data to predict TTP, such as the Bentley score, Coppo score, the PLASMIC score, and so on . Among the scores, the PLASMIC score has proved to be practical and effective, which was validated in some studies . However, according to our data, we found that the PLASMIC score may be not suitable to our Chinese suspected TTP patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation